Improving the Spectral Efficiency of Multiuser Multiple Antenna Millimeter Wave System Using Enhanced Kalman-Based Hybrid Precoder - Chioma Odochi Uneze; C. B. Mbachu; Chidiebere N. Muoghalu (Darul Yasin Al Sys, 2026)
Multipath fading remains a critical challenge in wireless communication systems, necessitating precoding schemes that are both flexible and robust under realistic transmission conditions. This study evaluated the performance of an enhanced Kalman-based hybrid digital precoding algorithm in a multipath environment with 10 paths and compared it with zero forcing (ZF), minimum mean square error (MMSE), and conventional Kalman hybrid digital precoding schemes reported in the literature. Using simulation-based analysis under varying numbers of base station (BS) antennas, the study assessed spectral efficiency as the primary performance indicator. The results showed that, at 64 BS antennas, the enhanced Kalman scheme outperformed ZF, MMSE, and Kalman precoding by 1.9711 bps/Hz, 1.7155 bps/Hz, and 1.11 bps/Hz, respectively. At 81 BS antennas, the corresponding performance gains were 1.7453 bps/Hz over ZF, 1.5344 bps/Hz over MMSE, and 0.9385 bps/Hz over Kalman. Similarly, at 256 BS antennas, the enhanced scheme achieved superior spectral efficiency by 1.4116 bps/Hz over ZF, 1.3324 bps/Hz over MMSE, and 0.9301 bps/Hz over Kalman. Overall, the findings demonstrate that the enhanced Kalman-based hybrid digital precoding algorithm consistently provides the highest spectral efficiency under identical multipath conditions, indicating improved data transmission performance over multipath communication channels. This study therefore contributes practical evidence for the application of enhanced Kalman-based precoding in wireless digital communication systems, with implications for achieving faster and more adaptable data transfer in realistic multipath environments.